Identification, expression, and association analysis of calcineurin B-like protein–interacting protein kinase genes in peanut - Ren, Weifang; Zhang, Juncheng; He, Jie; Fang, Jiahai; Wan, Liyun (Frontiers in Genetics, 2022)
Plants usually respond to the external environment by initiating a series of signal transduction processes mediated by protein kinases, especially calcineurin B-like protein-interacting protein kinases (CIPKs). In this study, 54 CIPKs were identified in peanut genome, of which 26 were from cultivated species (named AhCIPKs) and 28 from two diploid progenitors (Arachis duranensis - AdCIPKs, Arachis ipaensis - AiCIKs). Evolution analysis revealed that the 54 CIPKs were composed of two different evolutionary branches. The CIPK members were unevenly distributed at different chromosomes. The synteny analysis strongly indicated that whole-genome duplication (allopolyploidization) contributed to the expansion of CIPK genes. Comparative genomics analysis showed that there was only one common collinear CIPK gene pairs among peanut, Arabidopsis, rice, grape, and soybean. The prediction results of cis-acting elements showed that AhCIPKs, AdCIPKs, and AiCIPKs contained different proportions of transcription factors binding motifs involved in regulating plant growth, abiotic stress, plant hormones, and light response elements. Spatial expression profile revealed that almost all AhCIPKs had tissue-specific expression pattern. Furthermore, one polymorphic site in AdCIPK12 (AhCIPK11) was identified by association analysis which was significantly associated with PL (pod length), SL (seed length), HSW (hundred seed weight), and SR (shoot root ratio). Our results provide valuable information of CIPKs in peanut and facilitates better understanding of their biological functions.